The Determinants for Best Employability Skills and Job Opportunities for Undergraduate Students Majoring in Chinese in Thailand. Issue 7 (September 2019) - Jiracheewewong, Eknarin; Yongxia, MA; Han, XUE
Currently, those Thai universities offering Chinese majors do not include any specific provisions for employability training. This research was thus conducted using an employer survey ( N = 418) to determine employer needs and direct interviews with academics, students, and employers to identify the most effective training methods and how to integrate them into the curriculum. The survey identified the desirable skills and traits in graduates and their importance for successful fieldwork. The academic interviews determined which identified skills and traits can be enhanced using in-class and outside-class training. The proposed matrix model for three training approaches (internship, work experience, and outside activities) and their focuses was further refined via participant input. It is recommended that Thai university-level Chinese programs should implement more specific requirements for internships and external professional experience, including volunteer and student organization involvement.